Co-occurrence of related asexual, but not sexual, lineages suggests that reproductive interference limits coexistence - Whitton, Jeannette; Sears, Christopher J.; Maddison, Wayne P. (Proceedings of the Royal Society. B, Biological sciences, 2017)
We used randomizations to analyse patterns of co-occurrence of sexual and apomictic (asexual) members of the North American Crepis agamic complex (Asteraceae). We expect strong asymmetry in reproductive interactions in Crepis: apomicts produce clonal seeds with no need for pollination and are not subject to reproductive interference from co-occurring relatives. However, because they still produce some viable pollen, apomicts can reduce reproductive success of nearby sexual relatives, potentially leading to eventual local exclusion of sexuals. Consistent with this, randomizations reveal that sexuals are over-represented in isolated sites, while apomicts freely co-occur. Incorporation of taxonomic and phylogenetic evidence indicates that this pattern is not driven by local origins of asexuals. Our evidence that patterns of local co-occurrence are structured by reproductive interference suggests an underappreciated role for these interactions in community assembly, and highlights the need for explicit tests of the relative contributions of ecological and reproductive interactions in generating patterns of limiting similarity.